(3TQM BjI GdcQSjs - (3eMeO bGSe eMeO cGXe GdQTJjs
(3ChdgG (B:s
(3GdMeO ddg GdPj CNdi GaFOI GdYGQajf dJLdjGJ XghQg CeG HYO ajbhd Ef gPg cdeGJ hLjRI cJHJgG Ydi BjI GdcQSj hTQMJ HYV NaGjGgGs
(3BNQgG (B:s
(3hGdCQHYGA GdMSjf Ydjg GdSdGe hGdNejS GdbGFe GdegOj hGdSHJ GdRgQGA YdjgG GdSdGe s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs